Lactate dehydrogenase predicts disease progression outcome in COVID-19 patients treated with Azvudine - Mao, Manyun; Dian, Yating; Sun, Yuming; Chen, Wangqing; Zhu, Wu; Deng, Guangtong (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Azvudine has been approved in China for the treatment of COVID-19 patients. Previous studies have suggested a correlation between high levels of lactate dehydrogenase (LDH) and the severity of COVID-19. However, the impact of LDH levels in COVID-19 patients receiving Azvudine treatment remains unclear.In this retrospective cohort study, we analyzed the data of 351 hospitalized COVID-19 patients who were consecutively treated with Azvudine, with or without high LDH levels. The clinical features, treatment strategies and prognosis data were collected and analyzed.Results: Among the 351 hospitalized patients with COVID-19 treated with Azvudine (119 with high-LDH levels), the median age was 69 years (range 58-78), and 213 (60.7%) were male. Common symptoms included cough (86.0%), expectoration (73.5%), fever (69.8%), polypnea (47.6%) and poor appetite (46.4%). Patients with high LDH levels exhibited significantly elevated leucocyte and neutrophil counts, elevated level of myocardial enzymes, as well as higher levels of inflammatory markers such as interleukin-6, interleukin-10, procalcitonin, C reactive protein, ferritin, and prolonged erythrocyte sedimentation rate upon admission. COVID-19 patients with high-LDH levels had higher rates of corticosteroid therapy, non-invasive and invasive mechanical ventilation, worsened and death (2.5% vs. 0%). The Cox proportional hazard model demonstrated that high LDH levels (adjusted hazard ratio = 5.27; 95% confidence interval: 1.19, 14.50) were associated with a more unfavorable composite disease progression outcome among COVID-19 patients treated with Azvudine, after accounting for potential confounding variables.High-LDH levels predict a worse composite disease progression outcome in COVID-19 patients treated with Azvudine.